Minding the gap: of power and authority in hierarchical structures of multinational companies and its influence in wrongdoing - Foo, Yong Luk (2018)
This study positions itself to examine the influence of power and authority on the accountability of employees in Multinational Companies (“MNC”). To achieve this, this study will look at the relationship between an MNC’s hierarchical structure and employee wrongdoing. Along the way this paper will also examine the power gap in MNC and how best to avoid and mitigate the effects of scandals from employee wrongdoing.